2020
DOI: 10.1097/cce.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

Integral Use of Thromboelastography With Platelet Mapping to Guide Appropriate Treatment, Avoid Complications, and Improve Survival of Patients With Coronavirus Disease 2019–Related Coagulopathy

Abstract: Objectives: Coagulopathy of coronavirus disease 2019 is largely described as hypercoagulability, yet both thrombotic and hemorrhagic complications occur. Although therapeutic and prophylactic anticoagulant interventions have been recommended, empiric use of antifactor medications (heparin/enoxaparin) may result in hemorrhagic complications, including death. Furthermore, traditional (antifactor) anticoagulation does not address the impact of overactive platelets in coronavirus disease 2019. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 40 publications
1
40
0
4
Order By: Relevance
“…This may be a reflection of the fact that the massive inflammatory response seen in patients with COVID-19 has a greater impact on fibrinogen, von Willebrand Factor (vWF), and platelet levels, and less of an impact on coagulation factors. While the timelines of our literature search only identified one manuscript reporting the use of the TEG PlateletMapping assay to record platelet function [ 15 ], a recently published prospective study explored the use of thromboelastography with the platelet mapping algorithm to manage patients with COVID-19 [ 28 ]. The study found that the use of thromboelastography with platelet mapping could be used to characterize the spectrum of COVID-19 and reduced the risk for mechanical ventilation, acute kidney injury, and death ( p < 0.0001 versus non-algorithm-guided patients for all).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be a reflection of the fact that the massive inflammatory response seen in patients with COVID-19 has a greater impact on fibrinogen, von Willebrand Factor (vWF), and platelet levels, and less of an impact on coagulation factors. While the timelines of our literature search only identified one manuscript reporting the use of the TEG PlateletMapping assay to record platelet function [ 15 ], a recently published prospective study explored the use of thromboelastography with the platelet mapping algorithm to manage patients with COVID-19 [ 28 ]. The study found that the use of thromboelastography with platelet mapping could be used to characterize the spectrum of COVID-19 and reduced the risk for mechanical ventilation, acute kidney injury, and death ( p < 0.0001 versus non-algorithm-guided patients for all).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the use of thromboelastography with platelet mapping could be used to characterize the spectrum of COVID-19 and reduced the risk for mechanical ventilation, acute kidney injury, and death ( p < 0.0001 versus non-algorithm-guided patients for all). Using thromboelastography with platelet mapping to guide antiplatelet therapy treatment in patients with COVID-19 also decreased mortality by 82% ( p = 0.0002) [ 28 ]. However, studies of platelet function using multiple electrode aggregometry did not show any change in platelet aggregability in patients with COVID-19 [ 29 ], suggesting further observations are necessary to elucidate the role of platelet function in the etiology and progression of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various papers have shown the significance of TEG ® and the levels of coagulopathy in COVID-19 (an important measurement value of the TEG ® ) in managing COVID-19 patients is also getting more traction (Chandel, et al 2021, Görlinger and Levy 2021, Hranjec, et al 2020) (Smolarz, et al 2021). Hranjec and co-workers in 2020 also noted that TEG ® with platelet mapping, better characterizes the spectrum of COVID-19 coagulation-related abnormalities and may guide more tailored, patient-specific therapies these patients (Hranjec, et al 2020). Another important test is the PFA-200 platelet test.…”
Section: Significant Evidence For Hypercoagulation During the Early Stages Of Covid-19 Diseasementioning
confidence: 99%
“…In a study of 100 patients with COVID-19, the TEG platelet mapping assay (TEG-PM) results (maximum amplitude-arachidonic acid/adenosine diphosphate > 50 mm) were associated with thrombotic/ischemic complications and TEG-PM assay guided antithrombotic therapy (n = 72) was associated with decreased mortality (p = 0.0002) as compared to patients receiving non-guided therapy (n = 28) [ 19 ]. These results provide evidence to support the use of bedside viscoelastic assay in patients with COVID-19, but more evidence is needed to include this assay for routine measurement as a diagnostic and prognostic assay.…”
Section: Coagulation Testsmentioning
confidence: 99%